The Challenges and Opportunities for Developing Community-Based Tourism in Indonesia - Retno Dewi Pramodia Ahsani; Catur Wulandari; Chandra Dinata; Novia Amirah Azmi; Aqil Teguh Fathani (Universitas Sultan Ageng Tirtayasa, 2022)
This study aims to assess and elaborate on the problems and potential for accelerating the development of community-based tourism (CBT) in Banyuwangi, East Java Province. The faster human requirements are stimulating many innovations to boost revenue, particularly in improving the tourism sector by including the community in its development. Qualitative studies are specifically utilized to explain phenomena that occur when studying tourism industry issues, opportunities, and networks. In-depth interviews were conducted with 106 sources. The ecological indicators yield positive outcomes with AVE criteria of 0.674, natural resources of 0.473, human resources of 0.532, collaboration of 0.488, and benefits of 0.656. means that the chances in the Banyuwangi tourist sector still have a significant opportunity to improve and expand in the future, despite internal and external conflicts and promotional issues. They still provide opportunities to compete with other regional attractions. This fluctuation is supported by field confirmation, which indicates that while most sectors are operating normally, some destinations are experiencing difficulties. Governance, management, bureaucratic structure, collaboration, and promotion issues remain minor. The correlation of each variable and indicator employed in this study has its own interest, with 58 percent indicating prospects for tourism development.